2020
DOI: 10.1681/asn.2020010079
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease-Associated APOL1 Variants Have Dose-Dependent, Dominant Toxic Gain-of-Function

Abstract: BackgroundTwo coding renal risk variants (RRVs) of the APOL1 gene (G1 and G2) are associated with large increases in CKD rates among populations of recent African descent, but the underlying molecular mechanisms are unknown. Mammalian cell culture models are widely used to study cytotoxicity of RRVs, but results have been contradictory. It remains unclear whether cytotoxicity is RRV-dependent or driven solely by variant-independent overexpression. It is also unknown whether expression of the reference APOL1 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 27 publications
10
69
0
Order By: Relevance
“…There was significant enrichment for terms such as “mitochondrial inner membrane,” “oxidative phosphorylation,” “mitochondrial respiratory chain complex I,” “mRNA splicing,” and “ribonucleoprotein” ( Table S8 ). Previous studies have implicated mitochondrial dysfunction, abnormal energetics and reduced transcription in APOL1 associated FSGS 14-16, 21, 48, 49 . Given its large size and its enrichment for genes, subcellular structures, and pathways previously implicated in APOL1 FSGS, we focused on more deeply characterizing the Pink module and its submodules.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…There was significant enrichment for terms such as “mitochondrial inner membrane,” “oxidative phosphorylation,” “mitochondrial respiratory chain complex I,” “mRNA splicing,” and “ribonucleoprotein” ( Table S8 ). Previous studies have implicated mitochondrial dysfunction, abnormal energetics and reduced transcription in APOL1 associated FSGS 14-16, 21, 48, 49 . Given its large size and its enrichment for genes, subcellular structures, and pathways previously implicated in APOL1 FSGS, we focused on more deeply characterizing the Pink module and its submodules.…”
Section: Resultsmentioning
confidence: 97%
“…A major distinction between HR and LR FSGS related to differences in expression and/or co-expression of genes localized to mitochondrial compartments and/or processes. In the past decade, many experimental studies using inducible cell lines have linked increased HR APOL1 expression to mitochondrial dysfunction 14-16, 21, 48, 49 . Here, we extend these in vitro findings to patients with FSGS, increasing the relevancy and importance of dissecting these pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the participants recruited and samples collected in the NEPTUNE study provided us with a patient population and set of data with which to ask some fundamental questions about the relationship between APOL1 genotype, glomerular expression, and kidney tissue damage in unique ways: (1) the median age of the cohort at the time of biopsy was 16 years old (54% pediatric onset overall) which gave us a chance to study the morphologic consequences of APOL1 in a cohort younger than previously reported; (2) we restricted our cohort to only those of self-reported Black race or African genetic ancestry, which allowed us to make comparisons between risk genotypes and expression among these patients only. This prevented confounding by overall differences in genetic ancestry or by societal differences between races (e.g., structural racism against Black individuals) [28]; (3) the spectrum of patients with different number of risk alleles and available expression data gave us the opportunity to study whether single copies of risk variants and/or increased glomerular expression of APOL1 was associated with kidney damage, as reported in other studies [9,[29][30][31]; (4) This is a case-case study, which allows us to ask questions about how APOL1 may be causing a unique form of nephrotic syndrome, rather than a case-control study comparing APOL1-associated NS tissue to normal tissue; (5) the availability of 83 validated histologic and ultrastructural descriptors from light and electron microscopy created and measured as part of the NEPTUNE protocol allowed a level of morphologic granularity beyond that typically reported in clinical biopsy reports.…”
Section: Discussionmentioning
confidence: 99%
“…69 Hence it is possible that APOL1-G0 related protective cellular processes are "activated" in response to an external second stress, which explains why not all individuals with two copies of APOL1 G1 and/or G2 variants develop kidney disease. However, APOL1-G1 and -G2 appears to change cellular localization and oligomerization pattern 36 with associated cytotoxicity, which was not rescued by APOL1-G0 70 in in vitro studies suggesting that a dominant gain-of-function could also mediate CKD pathogenesis.…”
Section: Structure-function Correlation Of Apol1 Variants: Why Is It mentioning
confidence: 96%